Determinants of Users Intention to Use IoT - Baba, Nura Muhammad; Baharudin, Ahmad Suhaimi; Ayagi, Shehu Hassan; Ahmed, Abubakar Muaz; Sunusi, Ismail Basiru (International Journal of Psychosocial Rehabilitation, 2020)
The Internet of things (IoT) is realised as a potentially effective means of integrating multiple technologies to improve the quality of people’s life and offering interesting and advantageous new services to individuals. However, it has emerged that consumers’ acceptance of IoT is currently low despite its huge economic potentials and impacts, as well as high investment from the private and public sectors. Yet, few studies have investigated the perspectives of the users on IoT. Specifically, only a few empirical researches had examined the determinants of IoT service adoption from the user’s perspective and research model were still not fully developed. Hence, there is a dearth of empirical research on IoT adoption in Malaysia. Therefore, this research aims to develop an integrative model of factors influencing users’ acceptance of IoT. The research applied an integrated technology acceptance model (TAM). The research hope to provide useful insight into the key driving factors with regard to understanding consumers’ behavioural intention to use the IoT.